2022
DOI: 10.3390/curroncol29050252
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Adherence to Toxicity Management Guidelines for Immune-Related Adverse Events

Abstract: Immune checkpoint inhibitors (ICIs) affect immunologic homeostasis, leading to immune-related adverse events (irAEs). Early irAE detection and management can prevent significant morbidity and mortality. A retrospective chart review was performed to characterize irAEs associated with nivolumab, ipilimumab, and nivolumab plus ipilimumab in adult medical oncology patients in Nova Scotia Health-Central Zone from 2013–2020, and to describe adherence to toxicity management guidelines. Diarrhea/colitis, hepatitis, pn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Adding up, patients in PC often present with sarcopenia, which is another risk factor for irAEs (17). Since palliative treatment regimens are increasingly implemented nowadays, palliative patients are at high risk of developing late onset high grade irAEs more than six months after starting ICI treatment and need continuous follow-up care (8,20,21). Involving PC early on leads to better symptom control (22), timely end of life discussions and a reduction in readmissions to hospital which ameliorates the patients' overall quality of life (16)(17)(18)23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adding up, patients in PC often present with sarcopenia, which is another risk factor for irAEs (17). Since palliative treatment regimens are increasingly implemented nowadays, palliative patients are at high risk of developing late onset high grade irAEs more than six months after starting ICI treatment and need continuous follow-up care (8,20,21). Involving PC early on leads to better symptom control (22), timely end of life discussions and a reduction in readmissions to hospital which ameliorates the patients' overall quality of life (16)(17)(18)23).…”
Section: Discussionmentioning
confidence: 99%
“…Inpatient admission is often required in this setting. If an irAE is suspected or cannot be excluded, first-line therapy is the timely administration of corticosteroids (e.g., methylprednisolone 1-2 mg/kg/body weight) (20,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe dirAEs (grade 3 and grade 4) require the administration of high-dose systemic corticosteroid treatment, intense supportive care management, and wound management. In some cases, it is a must to administer tumor necrosis factor alpha (TNF-α) inhibitors (Infliximab or Etanercept), Mycophenolate mofetil, Cyclosporin, and even plasmapheresis [ 34 , 36 ] These reactions require a definitive interruption of immunotherapy [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prompt AEs management and, if possible, immunotherapy continuation are important since they might improve the patient’s prognosis as we demonstrated in the case report from our clinic [ 43 ]. For example, a study from Nova Scotia demonstrated that only half of immunotherapy-related AEs are managed according to guidelines and about 17% of discontinued patients were withdrawn too early for this reason [ 44 ]. The authors postulated that it may be caused by the aversion of some physicians to administer high-dose steroids, as it potentially may inhibit the immunotherapy effect.…”
Section: Discussionmentioning
confidence: 99%